Students’ Perception of Technological Media used by Teacher in Lerning English - Lubis, Fitriadi; Zainuddin (ELITE JOURNAL, 2025)
In the modern era, rapid technological development has significantly impacted various sectors, including education. One area that has undergone transformation is the use of technological media in English language learning. The integration of technology enables the teaching and learning process to become more effective, interactive, and tailored to students' needs. This study aimed to explore students’ perceptions of the technological media used by teacher in English language instruction at SMA Negeri 1 Kotanopan, Mandailing Natal Regency, North Sumatra. The population of this research were the ellevent grade science students. The sample was 33 students which selected by using random technique sampling. The research method employed was descriptive quantitative. Data were collected using a Likert-scale questionnaire, and the data analysis technique used was the mean score calculation. The distribution of students’ perception scores is as follows: High Category: 15.15%, Moderate Category: 69.70%, and Low Category: 15.15%. The results indicated that students’ perceptions of the use of technological media in English teaching were generally positive, with an average score of 73.